Whole-Genome Sequencing Provides Insight Into Antimicrobial Resistance and Molecular Characteristics of Salmonella From Livestock Meat and Diarrhea Patient in Hanzhong, China - Weng, Rui; Gu, Yihai; Zhang, Wei; Hou, Xuan; Wang, Hui; Tao, Junqi; Deng, Minghui; Zhou, Mengrong; Zhao, Yifei (Frontiers in Microbiology, 2022)
Salmonella is a major zoonotic pathogen, which usually contaminates food resulting in salmonellosis in humans. Exploring the characteristics and origins of Salmonella is essential in formulating prevention and control measures for Salmonella infection. We used slide agglutination, antimicrobial susceptibility testing and whole genome sequencing to analyze and compare Salmonella’s phenotype, genotyping diversity, and genetic relatedness from livestock meat and diarrhea patients in Hanzhong, China, from 2018 to 2020. Totally 216 Salmonella enterica isolates were screened from frozen whole chicken carcasses (44.3%, 70/158), frozen raw ground pork (36.2%, 59/163), and diarrhea patients (4.4%, 87/1964). Salmonella Typhimurium was the dominant serotype. Notably, compared with other sources, isolates obtained from frozen whole chicken carcasses showed significant resistance to third-generation cephalosporin and fluoroquinolones (p < 0.05). All strains were assigned into 36 sequence types (STs) and two novel STs, and an excellent consistency was observed between ST and serotype. Genomic data revealed that extended-spectrum β-lactamase genes were responsible for third-generation cephalosporin resistance in 52 Salmonella strains, and the most predominant resistance determinant was blaCTX-M. Furthermore, of the 60 CIP-resistant isolates, five single-base mutations in quinolone resistance-determining regions were identified in gyrA or in parC, and the plasmid-mediated quinolone resistance gene aac(6')Ib-cr was most often detected. The cgMLST clusters show that five clusters among four serotypes (including S. Typhimurium, S. London, S. Derby, and S. Agona) cover samples from diarrhea patient and livestock meat pathway isolate, indicating a possibility of cross-host transmission. In conclusion, the livestock meat isolates have more resistance than diarrhea patients isolates and maybe an essential source of human Salmonella infection.